Hubungan Pengetahuan Kepemimpinan Dengan Motivasi Perawat Dalam Hal Penugasan Dan Pelatihan Di Rumah Sakit - Maria Hariyati Oktaviani; Bambang Edi Warsito (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2018)
Motivation is not always obtained from a leader, but a nurse is able to be a leader in him/herself and in terms of caring for patients. This is very different from what happens in the field. Based on the findings in the field, it was found that there were still many leadership styles that did not focus on motivation in nurses' performance which had an impact on health services. Data supporting based on research conducted by the Directorate of Nursing at the Ministry of Health of the Republic of Indonesia found that 70% of nurses during the last 3 years had never attended training, 39.8% were still doing cleaning tasks, 47.4% nurses and midwives did not have job descriptions and not developed monitoring and performance evaluation of nurses and midwives especially regarding skills, attitudes, discipline and work motivation. Based on the results of research from several journals, namely motivation that gives influence to the performance of nurses, especially in terms of employment, shows that there is similarity in the terms of leadership knowledge relations with low nurse motivation in terms of assignments and training. Lack of motivation in terms of assignments and training that can lead to a lack of nurse knowledge in terms of health services